Influence of canine brain decomposition on laboratory diagnosis of rabies. - Albas, A.; Ferrari, C. I.; da Silva, L. H.; Bernardi, F.; Ito, F. H. (FapUNIFESP (SciELO), 1999)
Canine brains infected with rabies virus were submitted to decomposition by being left at room temperature of 25 to 29 degrees C for up to 168 h. At 24 h intervals, brain fragments were analyzed by immunofluorescence (IF) and by the mouse intracerebral inoculation (MI) test to confirm the diagnosis of rabies and to measure the putrefaction effect on the accuracy of the diagnosis. Forty eight h after the beginning of the experiment, the MI test showed signs of impairment with four negative results, while after 72 h, 100% of the results were negative to the MI test and only one result was negative to the IF test, indicating that the threshold period for accurate diagnosis is 24 to 48 h before putrefaction. The authors recommend the shipment of suspected cases of rabies to the laboratory for confirmation, but the use of putrid materials for diagnosis is meaningless because of false-negative results.
Keywords: animal; animal disease; brain; dog; dog disease; fluorescent antibody technique; laboratory; mouse; pathology; rabies; standard; temperature; time; virology; Animals; Brain; Dog Diseases; Dogs; Fluorescent Antibody Technique; Laboratories; Mice; Rabies; Temperature; Time Factors